ANALYSIS OF RECEIVABLES ON SALES OF VASAKA NINES DEVELOPMENT PROJECTS AT PT. WASKITA KARYA REALTI - Galih Maharani Putri (2020)
This study focuses on the sales receivables of Nines Plaza & Residence Apartments which are guided by PSAK 71. The goal to be achieved by researchers in this case is to answer related receivables on sales of Nines Plaza & Residence Apartments at PT. Waskita Karya Realty. This study uses qualitative methods with interpretive paradigms and with ethn methodological approaches. From this study data collection techniques were carried out by interviewing key information and supporting informants, observation and documentation. The results of this study are PT. Waskita Karya Realty receivables analysis method uses the calculation of the age of receivables that the level of collectability of receivables tends to increase receivables that can be collected by the company to the buyer as a result of credit sales transactions. related to covid that is happening Nines Plaza & Residence Apartment applies a billing in the form of cash in providing relief to consumers to make payments 50% or 60% of the bill that has been set every month, and no fines are given to consumers during the covid pandemic 19.